Manajemen Diri dalam Perspektif Pendidikan Islam - Arani, Rohmawati; Ginanjar, Wahyu; Farida, Neng Awalia (Perkumpulan Peneliti dan Pegiat Literasi, 2022)
The human self has the necessity of life to regulate life in order to achieve happiness as the goal of life. Education is a means and provision to achieve and make it happen if it is accompanied by positive and beneficial actions for oneself and others. Education will be effective if the perpetrators, both students (students) and teachers, direct students to achieve this goal which is called self-management. Self-management means placing everything regularly in life, in the use of time, choices, interests, activities, and in physical and mental balance. It also means pushing oneself forward, managing all the personal elements, controlling the potential will to achieve good things, and developing various aspects of personal life to make it more perfect. This paper aims to present self-management from an educational perspective. This research is library research, which is research based on searching the literature related to the issues to be discussed. The data in this library research is obtained through digging and tracing books, articles, magazines, journals, internet access and other important related notes. The results of this study reveal that self-management as meant in this paper is the personal ability of students or educators to achieve certain goals including learning must be managed appropriately, according to the concept of management, that self-management is a skill and expertise of a person that is contained within. One way that can be done as a self-management application in the educational process can be seen from the indicators; such as the ability to determine learning objectives, the ability to monitor and evaluate learning objectives, and be able to motivate and provide self-reinforcement.